Review of the Mediating Role of Satisfaction on the Influence of Service Quality, Brand Image, and Trust on the Loyalty of BPJS Employment Participants in Situbondo - Vivi Arsita Wulandari; Deasy Wulandari; Hari Sukarno (Harmony Management: International Journal of Management Science and Business, 2025)
This study aims to analyze the effect of service quality , brand image , and trust on the loyalty of BPJS Ketenagakerjaan participants in the Non-Wage Recipient (BPU) segment at the Situbondo Branch, with satisfaction as a mediating variable. The research method uses a quantitative approach with purposive sampling techniques and data collection through questionnaires distributed to 110 respondents who have been active participants for more than six months. Data analysis was carried out using the Structural Equation Modeling Partial Least Square (SEM-PLS) method. The results of the study indicate that service quality and trust have a significant effect on satisfaction, while brand image does not have a significant effect. Meanwhile, trust and satisfaction have a significant effect on loyalty, while service quality and brand image do not. Satisfaction is also proven to mediate the effect of trust on loyalty, but does not significantly mediate other variables. This finding implies that increasing participant trust and satisfaction is the main key in building BPU participant loyalty at BPJS Ketenagakerjaan Situbondo.